V’s DIAMOND: AN INNOVATIVE FRAMEWORK FOR ASSESSING THE COMPETITIVE ADVANTAGES OF FISH PROCESSING INDUSTRY CLUSTERS IN ARCHIPELAGIC REGIONS - Kakerissa, Ariviana Lientje (Fakultas Teknik Universitas Pattimura, 2025)
The fish processing sector on Ambon Island faces significant challenges in strengthening its competitiveness in both domestic and international markets. This study introduces the V’s Diamond model, an adaptation of Porter’s Diamond that integrates social capital as a key element in assessing the competitiveness of fish processing industry clusters in archipelagic regions. The research aims to develop and apply this model to Ambon Island, evaluating its relevance and implications for small island economies. A mixed-methods approach was employed, combining interviews with industry stakeholders, government representatives, and trade associations with an extensive literature review. Findings highlight the critical role of infrastructure, raw material availability, government policies, and social capital in enhancing the competitiveness of the fish processing industry cluster. The incorporation of social capital within the V’s Diamond framework emphasizes the importance of collaboration in driving efficiency and innovation. Based on these insights, the study offers strategic recommendations to strengthen the fish processing industry on Ambon Island and explores the model’s broader applicability to other archipelagic regions.